The Australasian Psoriasis Collaboration view on methotrexate for psoriasis in the Australasian setting. (12th July 2016) - Rademaker, Marius; Gupta, Monisha; Andrews, Megan; Armour, Katherine; Baker, Chris; Foley, Peter; Gebauer, Kurt; George, Jacob; Rubel, Diana; Sullivan, John
Abstract: The Australasian Psoriasis Collaboration reviewed methotrexate (MTX) in the management of psoriasis in the Australian and New Zealand setting. The following comments are based on expert opinion and a literature review. Low‐dose MTX (< 0.4 mg/kg per week) has a slow onset of action and has moderate to good efficacy, together with an acceptable safety profile. The mechanism of action is anti‐inflammatory, rather than immunosuppressive. For pretreatment, consider testing full blood count (FBC), liver and renal function, non‐fasting lipids, hepatitis serology, HbA1c and glucose. Body mass index and abdominal circumference should also be measured. Optional investigations in at‐risk groups include an HIV test, a QuantiFERON‐TB Gold test and a chest X‐ray. In patients without complications, repeat the FBC at 2–4 weeks, then every 3–6 months and the liver/renal function test at 3 months and then every 6 months. There is little evidence that a MTX test dose is of value. Low‐dose MTX rarely causes clinically significant hepatotoxicity in psoriasis. Most treatment‐emergent liver toxicity is related to underlying metabolic syndrome and non‐alcoholic fatty liver disease or non‐alcoholic steatohepatitis. Alcohol itself is not contraindicated, but should be limited to < 20 gm/day. [Correction added on 6 January 2017, after first online publication: '20 mg/day' has been corrected to '20 gm/day'.] Although MTX is a potential teratogen post‐conception, there is little evidence for this pre‐conception. MTX does not affect the quality of sperm. There is no evidence that MTX reduces healing, so there is no specific need to stop MTX peri‐surgery. MTX may be used in combination with cyclosporine, acitretin, prednisone and anti‐tumour necrosis factor biologics.